Evaluacija odnosov z javnostmi - Kocjanc, Damjana (Teorija in praksa, 1999)
Article presents an overview of use of evaluation theory in public relations. Need for public relations evaluation is growing rapidly during last few years. Reasons for that fact could be found in the growing reputation of public relations, in dissatisfaction of managers because of untagible results of public relations, their demands for justification of growing costs for realization of public relations programmes and in other factors.
Keywords: odnosi z javnostjo; vrednotenje; raziskovanje